2015
DOI: 10.1016/j.chembiol.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Sterols Are Suicide Inhibitors of Ergosterol Biosynthesis and Growth in Trypanosoma brucei

Abstract: SUMMARY Trypanosoma brucei, the causal agent for sleeping sickness, depends on ergosterol for growth. Herein, we describe the effects of a mechanism-based inhibitor, 26-fluorolanosterol (26FL), which converts in vivo to a fluorinated substrate of the sterol C24-methyltransferase essential for sterol methylation and function of ergosterol and missing from the human host. 26FL showed potent inhibition of ergosterol biosynthesis and growth of procyclic and bloodstream forms while it has no effect on cholesterol b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 51 publications
3
38
1
Order By: Relevance
“…To examine the properties of the two Ac SMTs, a soluble enzyme extract was prepared by methods previously employed in the study of protozoa SMT cloned and expressed in bacterial cells that do not synthesize sterols. Although we observed increasing enrichment of Ac SMT during purification by SDS-PAGE (data not shown), differential loss of SMT activity as noted in previous studies in SMT purification can occur, yielding homogenous SMT with a low turnover number of ∼0.6 min −1 ( 15 , 16 , 19 ). Recently, we determined the reason for major loss of activity during protein purification is attributable to the allosteric nature of SMT (homotetramer showing cooperativity among its subunits), which contains a Walker motif for ATP binding in the SMT sequence.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…To examine the properties of the two Ac SMTs, a soluble enzyme extract was prepared by methods previously employed in the study of protozoa SMT cloned and expressed in bacterial cells that do not synthesize sterols. Although we observed increasing enrichment of Ac SMT during purification by SDS-PAGE (data not shown), differential loss of SMT activity as noted in previous studies in SMT purification can occur, yielding homogenous SMT with a low turnover number of ∼0.6 min −1 ( 15 , 16 , 19 ). Recently, we determined the reason for major loss of activity during protein purification is attributable to the allosteric nature of SMT (homotetramer showing cooperativity among its subunits), which contains a Walker motif for ATP binding in the SMT sequence.…”
Section: Resultssupporting
confidence: 67%
“…9C ), gave for the intercept a maximum rate of inactivation of ∼0.4 min −1 and T 1/2 of 17 min. The partition ratio ( k cat / k inact ), a measure of formation of C26 methyl monol product per inactivation event, generated by 24-SMT incubated with DHL is ∼1, which is close to the partition ratio of 3 for 26-flourocholesta-5,7,24-trieniol against Tb SMT ( 16 ), suggesting DHL is a potent inactivator of Ac SMT activity. Selectivity of the time-dependent nature of covalent inhibitors such as DHL with their target proteins is often measured as k inact / K i values in preference to IC 50 values ( 12 ).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…rhodesiense bloodstream forms in vitro [60]. Different enzyme inhibitors targeting CYP51 and C24-methyltransferase have also been identified [18,6163]. Posaconazole is a potent inhibitor of the Cyp450-dependent lanosterol 14α-demethylase in yeasts and molds [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported 24-Methylenecyclopropane as new class of steroidal inhibitors-mechanism-based suicide substrates with promising activity against T. brucei [26]. It would be interesting to investigate 24-methylene cholesterol as inhibitor of ergosterol biosynthesis as potential drug target [27]. …”
Section: Antiprotozoal Activitymentioning
confidence: 99%